Medição do desgaste de brocas helicoidais de aço rápido por meio do uso de um dispositivo a laser - Fortunato, Fernando Aparecido Pacheco da Silva (2012)
This work shows how the wear of high speed steel twist drill bits, can be measured through the use of a LASER (Light Amplification by Stimulated Emission of Radiation). Drilling tests were carried out on specimens made from 4340 steel, using drills with diameter of 10 mm. The machine used in the tests was a CNC (Computer Numerical Control) machining centre, fitted with a LASER Toolsetter. The measurement took place after the execution of one or more holes; the bit that was in rotation scheme is paralyzed, then the main axis where the tool was fixed, moves up the device responsible for measurement, partially interrupting the emission of the LASER beam. Distance learning generated by the interruption of the drill was converted by the electronic system, Toolsetter for numeric values. The data generated in trials were collected by information capture software installed on a notebook, which was connected via USB cable to Toolsetter. The information was handled, to allow the generation of graphs of dimensional variations of the tool. The drills used in the trials were photographed, and measures with the aid of a software Computer Aided Design (CAD), to highlight the existence of dimensional variations in the tool. Through this research, data studied concludes that the use of a LASER device is effective in the measurement of wear and other dimensional variations, present in high speed steel twist drills, after drilling operations.